Fashioning the 'Performance Man': Costumes and contexts of Andrey Bartenev. Issue 1 (1st September 2019) - Vainshtein, Olga
The article is focused around the work of contemporary Russian artist Andrey Bartenev. Nicknamed the 'Performance Man' and the 'Master of Installations', Bartenev creates performances, installations, kinetic sculptures, theatrical and video art and flamboyant outfits for himself. The article argues that expressive aesthetics of Bartenev's performances are connected to the culture of Russian avant-garde. The methodological frame of analysis includes the concept of Bakhtinian grotesque, demonstrating the liberating and subversive potential of carnivalesque culture. Special attention is given to representations of body in Bartenev's performances. Many of his performances feature a carnival grotesque body: oversized, unnaturally tall, asymmetrical, covered with various bulges. The origin of Bartenev's individual fashion style is interpreted in the historical context. The article explores Bartenev's views on the transience of performance, on the role of positive emotions in performances and on environmental pollution and ideas of sustainability.